Indonesian Spelling Errors in the Text of Observation Report Written by Students - Munira, Faiza; Utami, Santi Pratiwi Tri (J-LELC: Journal of Language Education, Linguistics, and Culture, 2025)
correct spelling, such as the use of capital letters at the beginning of words at the beginning of a sentence, is an important aspect of language skills that must be possessed by students. The results of the observation show that the application of spelling by students is still often an obstacle in writing activities. The purpose of this study is to identify and analyze Indonesian spelling errors in the observation report text of students' work in grades VIII C and D of SMP Negeri 30 Semarang. In addition, this study also describes the factors causing these errors as well as the stages and forms of improvement. This is important to explore because the use of Indonesian spelling in accordance with EYD V is still an obstacle in writing, especially writing observation report texts. This study uses a qualitative descriptive approach with data collection techniques in the form of interviews and documentation studies. The results of the study show various spelling errors in Indonesian made by students including errors in the use of capital letters, punctuation, hyphenation, writing of loan words, affixed words, abbreviations, numbers, and pronouns. The process of correcting these errors is carried out through several stages, namely identification, analysis, and error correction. Factors that influence these errors include poor understanding of EYD V, unintentional, and lack of seriousness of students in writing. This study is useful as evaluation material for educators to improve the quality of Indonesian language learning, especially in the linguistic aspect, as learning for students regarding language errors, and can be used as a reference for further researchers related to similar research.